Predictors of occupational stress among teachers in Rupandehi, Nepal - Dhungana, M; Shrestha, R; Kafle, B; Shrestha, R (Devdaha Medical Journal, 2025)
Introduction: Occupational stress among school teachers is a global concern, driven by psychosocial challenges that contribute to psychological distress. Nepal, a developing country, has limited findings or data on teacher’s stress. This study aims to assesses the prevalence and predictors of occupational stress among school teachers in Rupandehi, Nepal, because chronic stress can lead to burnout, reduced job satisfaction, health problems and ultimately affecting the quality of teaching and student outcomes.Methods: A cross-sectional study was conducted in June 2021 among 80 secondary-level teachers using enumerative sampling technique at Kanti Higher Secondary School, Butwal, Rupandehi, Nepal. The 14-item Perceived Stress Scale (PSS-14) was used to measure the stress levels. Socio-demographic and occupational variables were analyzed using IBM SPSS Statistics v16, with chi-square tests to assess associations.Results: Of the 80 teachers, 18 (22.5%) reported low stress, 48 (60.0%) moderate stress, and 14 (17.5%) high stress. Gender (χ²=6.89, p=0.032) and teaching level (χ²=5.98, p=0.048) were significantly associated with stress levels, while age (p=0.356), marital status (p=0.345), and years of experience (p=0.342) were not associated.Conclusion: This study found that more than half of school teachers reported experiencing moderate stress (60%), mild stress (22.5%) and high stress (17.5%) level. Gender and teaching level as key predictors. Institutional reforms, mental health assessments, and targeted interventions are essential to enhance teachers’ psychological wellbeing in developing countries like Nepal.